STRATEGI NAFKAH ISTRI NELAYAN BURUH DI DESA PENGAMBENGAN KECAMATAN NEGARA KABUPATEN JEMBRANA - Wilda Magfiroh; Sofia Sofia (University of Jember, 2020)
Labor fishermen are the lowest element of social structure in the fishermen community. The unstable income of labor fishermen because of the season and weather conditions makes their wives work in the public sector to support their household income. This research aims to identify the motivation of the labor fishermen's wives to work in the public sector and to find out their livelihood strategies. The location of the research was determined purposively, namely Pengambengan Village, Negara District, Jembrana Regency, Bali Province. This research used a descriptive and qualitative approach. The key informant was selected purposively while supporting informants were selected by using the snowball sampling technique. The data were collected by using methods of interview, observation and document were analyzed using the Miles and Huberman model. The results showed that 1) the motivation of the fishermen's wives to work in the public sector included physiological needs, safety needs, and social needs. 2) There were two livelihood strategies undertaken by labor fisherman wives, namely livelihood diversification through working as traders, tailors, and labor; migration through working outside the village as a laborer in the agricultural sector. Keywords: Labor Fishermen's Wife, Motivation, Livelihood Strategy, Diversification, Migration